(untitled) (Ameghiniana, 2013)
A new spore species, Muricingulisporis chenqucnsis is described upon material recovered from Tertiary deposits of the Cheuque Formation (Chubut province, Argentina). lt probably belongs to the Pteridaceae; comparisons with fossil and extant taxa are made and a likely evolutive line, from Cretaceous to Recent time, is suggested. Finally its possible palaeoenvironmental significance is briefly analysed.